2010
DOI: 10.1097/ajp.0b013e3181e104f2
|View full text |Cite
|
Sign up to set email alerts
|

Fear-avoidance and Endurance-related Responses to Pain: New Models of Behavior and Their Consequences for Clinical Practice

Abstract: Although both, fear-avoidance and endurance responses have been identified in patients with chronic musculoskeletal pain, currently evidence to confirm their hypothesized consequences for daily functioning is incomplete. Finally, thoughts on the development of differentially targeted and individually scheduled behavioral interventions are reported, including suggestions for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
241
1
14

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(271 citation statements)
references
References 58 publications
15
241
1
14
Order By: Relevance
“…Avoidance behavior is considered a relatively stable response driven by a fear-based motivation to prevent further injury. 9,18,29,54 However, the results of the current study show that avoidance can be influenced by the presence of concomitant, competing goals, such as the goal to retrieve a reward, even without changing pain-related fear itself. 23,40,44,47,49 Thus, avoidance behavior may vary from situation-to-situation, also even within individuals.…”
Section: Discussionmentioning
confidence: 56%
“…Avoidance behavior is considered a relatively stable response driven by a fear-based motivation to prevent further injury. 9,18,29,54 However, the results of the current study show that avoidance can be influenced by the presence of concomitant, competing goals, such as the goal to retrieve a reward, even without changing pain-related fear itself. 23,40,44,47,49 Thus, avoidance behavior may vary from situation-to-situation, also even within individuals.…”
Section: Discussionmentioning
confidence: 56%
“…One possible reason for these incongruent findings is that fear-avoidance models consider avoidance as a relatively stable behaviour pattern [13]. Largely neglected, however, is that avoiding pain is often only one goal in a dynamic environment with concomitant, competing goals [15,38,46].…”
Section: Introductionmentioning
confidence: 86%
“…We found that avoidance of pain was inhibited when a competing task-related goal (i.e., earning money) was activated. Current models of disability [13,44] consider pain-related avoidance as a relatively stable behaviour pattern. The present findings suggest that such view might be too narrow, and that pain behaviour should be considered within a dynamic environment of concomitant, often competing, goals [15,38,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may be motivated to ignore the pain and to stay committed to earlier activities and life goals (persistence). Indeed, there is evidence that some patients persist in their activities despite pain 15 . At first sight, it seems adaptive to prevent interference by pain and to continue with activities.…”
Section: Coping With Pain Re-visited: the Pursuit Of Valued Activitiementioning
confidence: 99%